2017
DOI: 10.3390/genes8100282
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Synapsis and Recombination in Male Hybrids between Two Chromosome Races of the Common Shrew (Sorex araneus L., Soricidae, Eulipotyphla)

Abstract: Hybrid zones between chromosome races of the common shrew (Sorex araneus) provide exceptional models to study the potential role of chromosome rearrangements in the initial steps of speciation. The Novosibirsk and Tomsk races differ by a series of Robertsonian fusions with monobrachial homology. They form a narrow hybrid zone and generate hybrids with both simple (chain of three chromosomes) and complex (chain of eight or nine) synaptic configurations. Using immunolocalisation of the meiotic proteins, we exami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
4
9
0
Order By: Relevance
“…Nevertheless, the latter one and F 1 hybrids differed significantly ( p < 0.001). Our results are consistent with previously published data from the Tomsk–Novosibirsk hybrid zone (Belonogova et al, 2017).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Nevertheless, the latter one and F 1 hybrids differed significantly ( p < 0.001). Our results are consistent with previously published data from the Tomsk–Novosibirsk hybrid zone (Belonogova et al, 2017).…”
Section: Resultssupporting
confidence: 94%
“…Nonetheless, in cases of normal centromeres, the number of recombination nodules in multivalents was close to normal (approaching the expected value). Similar results have been reported about the Drnholec-Białowieża (Jadwiszczak & Banaszek, 2006) and Tomsk-Novosibirsk F 1 hybrids (Belonogova et al, 2017).…”
Section: Recombination Of Shrew Meiotic Cxis Likely Leads To Balanced...supporting
confidence: 89%
See 2 more Smart Citations
“…We propose that these chromosomal alterations result from the formation of multivalent associations during meiosis I of specimens of the F1 generation (females). Interspecific hybrids resulting from the crossing of highly divergent species in relation to chromosomal structure, commonly present high structural heterozygosity, and formation of chains and meiotic rings [ 35 , 36 ]. Probably, F1 hybrids originated by crossing the two Trichechus species analyzed in this article fit this context, since our G-banding comparison between TIN and TMM showed that these sirenians are divergent by at least five Robertsonian rearrangement events and by the pericentric inversion of pair 1.…”
Section: Discussionmentioning
confidence: 99%